Herpetofauna in Ranu Darungan and Blok Ireng-Ireng, Bromo Tengger Semeru National Park: Before-After the COVID-19 and Eruption - Hanifa, Berry Fakhry; Aini, Quratul; Hasyim, Muhammad Asmuni; Septiadi, Luhur (Jurnal Sylva Lestari, 2024)
The continuous eruption of the Bromo Tengger Semeru volcanic complex may have impacted the overall biodiversity in Bromo Tengger Semeru National Park, including amphibians and reptiles. On the other hand, restrictions on traveling during the COVID-19 pandemic may positively impact nature by minimizing the tourism-disturbance. This study analyzes the diversity of reptiles and amphibians before and after COVID-19 and Semeru eruption at Ranu Darungan and Blok Ireng-Ireng (utilization zone) of Bromo Tengger Semeru National Park during three continuous surveys (2019, 2021, and 2022). Preliminary sampling was conducted in August 2021, whereas extensive sampling was carried out in March–May 2022 using a visual encounter survey on two habitat conditions (terrestrial and aquatic); we used previous survey data for 2019. The continuous surveys in Ranu Darungan and Blok Ireng-Ireng showed the herpetofauna diversity consisting of 19 amphibian species (6 families) and 11 reptile species (5 families), where sampling effort in 2022 was adequate to reflect the overall herpetofauna diversity. There was a decrease in the species diversity index in Ranu Darungan after the Semeru eruption, indicating an increase in environmental stress for amphibians. However, the expected trend was not observed before and after the COVID-19 pandemic; other factors (besides reduced human activity at the site) may have contributed. Keywords: amphibian, diversity, herpetofauna, national park, reptile